Integrative miRNA and mRNA analysis in penile carcinomas reveals markers and pathways with potential clinical impact - Kuasne, Hellen [UNESP]; Barros-Filho, Mateus C.; Busso-Lopes, Ariane; Marchi, Fábio A.; Pinheiro, Maisa; Muñoz, Juan J.M.; Scapulatempo-Neto, Cristovam; Faria, Eliney F.; Guimarães, Gustavo C.; Lopes, Ademar; Trindade-Filho, José C.S. [UNESP]; Domingues, Maria Aparecida C. [UNESP]; et al. (Impact Journals, 2017)
Penile carcinoma (PeCa) is an important public health issue in poor and developing countries, and has only recently been explored in terms of genetic and epigenetic studies. Integrative data analysis is a powerful method for the identification of molecular drivers involved in cancer development and progression. miRNA and mRNA expression profiles followed by integrative analysis were investigated in 23 PeCa and 12 non-neoplastic penile tissues (NPT). Expression levels of eight miRNAs and 10 mRNAs were evaluated in the same set of samples used for microarray and in a validation set of cases (PeCa = 36; NPT = 27). Eighty-one miRNAs and 2,697 mRNAs were identified as differentially expressed in PeCa. Integrative data analysis revealed 255 mRNAs potentially regulated by 68 miRNAs. Using RT-qPCR, eight miRNAs and nine transcripts were confirmed as altered in PeCa. We identified that MMP1, MMP12 and PPARG and hsa-miR-31-5p, hsa-miR-224-5p, and hsa-miR-223-3p were able to distinguish tumors from NPT with high sensitivity and specificity. Higher MMP1 expression was detected as a better predictor of lymph node metastasis than the clinical-pathological data. In addition, PPARG and EGFR were highlighted as potential pathways for targeted therapy in PeCa. The analysis based on HPV positivity (7 of 23 cases) revealed five miRNA and 13 mRNA differentially expressed. Although in a limited number of cases, HPV positive PeCa presented less aggressive phenotype in comparison with negative cases. Overall, an integrative analysis using mRNA and miRNA profiles revealed markers related with tumor development and progression. Furthermore, MMP1 expression level was a predictive marker for lymph node metastasis in patients with PeCa.
Keywords: HPV infection; Integrative analysis; Lymph node metastasis; Micro-RNA; Penile carcinoma